Performance analysis of machine learning libraries - Kędziora, Ewa Justyna; Maksim, Grzegorz Krzysztof (Journal of Computer Sciences Institute, 2021)
The paper presents results of performance analysis of machine learning libraries. The research was based on ML.NET and TensorFlow tools. The analysis was based on a comparison of running time of the libraries, during detection of objects on sets of images, using hardware with different parameters. The library, consuming fewer hardware resources, turned out to be TensorFlow. The choice of hardware platform and the possibility of using graphic cores, affecting the increase in computational efficiency, turned out to be not without significance.